The bishop of Winchester, the abbey of Titchfield and the ‘Pretended Chapel’ of Hook, 1375–1405 - Given-Wilson, Chris (People, Power and Identity in the Late Middle Ages: Essays in Memory of W. Mark Ormrod, 2021)
The first known reference to it is dated 15 March 1364, when Pope Urban V ordered Bishop Edington of Winchester to inquire into a petition from the inhabitants of Hook proposing the foundation of a chapel there. The problem was that neither Bishop Wykeham nor the abbot of Titchfield to whom the parish church had been appropriated since the abbey's foundation in 1232 supported the construction of a chapel at Hook; and therein lay the origins of the dispute. The contention of the abbot of Titchfield, John de Thorney, supported by Wykeham, was that the chapel at Hook prejudiced the rights of both the abbey and the parish church. At some point during the later fifteenth century, the chapel for which William Maple, John Michol and the villagers had fought so doggedly seems simply to have become surplus to requirements, and by the time Titchfield Abbey was suppressed in 1537 it was barely even a memory.
Num Pages: 20
Keywords: titchfield

The Last Days of the Abbeys of Durford and Titchfield and a Case of Mistaken Identity - Stevenson, Janet H. (Proceedings of the Hampshire Field Club and Archaeological Society, 2016)
Keywords: durford; titchfield

Two dated monastic buildings at Titchfield - Roberts, Edward (Hampshire studies, 2000)
Keywords: titchfield

Peasant discontent on the manors of Titchfield abbey, 1245-1405 - Watts, D. George (Proceedings of the Hampshire Field Club and Archaeological Society, 1983)
Keywords: titchfield

The villages on the manors of Titchfield abbey - Watts, D. G. (Proceedings of the Hampshire Field Club and Archaeological Society, 1958)
Keywords: titchfield

The estates of Titchfield Abbey, c. 1245 to c. 1380 - Watts, D. G. (University of Oxford, 1957)
Keywords: titchfield

Mediaeval Tiles at Titchfield Abbey, Hants., Afterwards Place or Palace House - Green, P.M.; Green, A.R. (Hampshire Field Club, 1949)
Keywords: titchfield

The medieval library of Titchfield Abbey - Wilson, Richard M. (Chorley & Pickersgill, 1940)
Keywords: titchfield

Premonstratensian Itineraries from a Titchfield Abbey Manuscript at Welbeck - Dickins, Bruce (Proceedings of the Leeds Philosophical and Literary Society. Literary and Historical Section., 1938)
Keywords: titchfield

The Catalogue of Titchfield Abbey - Hautenville-Cope, J. (Proceedings of the Hampshire Field Club and Archaeological Society, 1916)
Keywords: titchfield

The Making of Place House at Titchfield, Near Southampton, in 1538 - John Hope, W. H. St. (Archaeological Journal, 1906)
Publisher: Routledge _eprint: https://doi.org/10.1080/00665983.1906.10853030
Keywords: titchfield

Houses of Premonstratensian canons: Abbey of Titchfield - Doubleday, H. Arthur; Page, William (A History of the County of Hampshire, 1903)
Keywords: titchfield

On an Ancient Deed Between the Abbot of Titchfield and the Monks of Quarr - Prideaux-Brune, E.S. (Papers and Proceedings of the Hampshire Field Club and Archaeological Society, 1903)
Keywords: titchfield

Titchfield Abbey and Place House - Minns, G.W. (Proceedings of the Hampshire Field Club & Archaeological Society, 1898)
Keywords: titchfield

Abbats [sic] of Tichfield Abbey, in Hampshire - Madden, F. (Collectanea Topographica et Genealogica, 1834)
Keywords: titchfield